2022
DOI: 10.1161/strokeaha.121.036233
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Factors for Spontaneous Intracerebral Hemorrhage: A Case-Crossover Study

Abstract: Background and Purpose: Whether certain activities can trigger spontaneous intracerebral hemorrhage (ICH) remains unknown. Insights into factors that trigger vessel rupture resulting in ICH improves knowledge on the pathophysiology of ICH. We assessed potential trigger factors and their risk for ICH onset. Methods: We included consecutive patients diagnosed with ICH between July 1, 2013, and December 31, 2019. We interviewed patients on their exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…However, intake of caffeine may temporarily increase the blood pressure in individuals with hypertension, which may lead to an increased risk of intracranial hemorrhage in hypertensive individuals ( 8 , 40 ). A recently published study confirmed that coffee consumption is the main trigger factor for intracranial hemorrhage ( 41 ). Although caffeine could reinstate the adenosine-inhibited synaptic excitatory signaling in human neurons, it also could attenuate synaptic long-term potentials ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 93%
“…However, intake of caffeine may temporarily increase the blood pressure in individuals with hypertension, which may lead to an increased risk of intracranial hemorrhage in hypertensive individuals ( 8 , 40 ). A recently published study confirmed that coffee consumption is the main trigger factor for intracranial hemorrhage ( 41 ). Although caffeine could reinstate the adenosine-inhibited synaptic excitatory signaling in human neurons, it also could attenuate synaptic long-term potentials ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 93%
“…40 In contrast to previous studies in older populations, coffee consumption was not identified as a trigger factor for any type of stroke in our young population. 13,16,24 A possible explanation may be that the effect of a sudden blood pressure surge differs between old and young people, with the elderly individuals more often having long-standing hypertension, atherosclerosis, and reduced vessel wall elasticity. 41,42 In line with previous literature, we did not find cigarette smoking as a trigger factor and even found a negative relative risk.…”
Section: Discussionmentioning
confidence: 99%
“…23,34,35 Conversely, a sudden rise in blood pressure might trigger rupture of a vessel wall, resulting in an ICH. 13,16 In addition, some drug types are known to cause vasospasms without a blood rise, which can also lead to stroke. 36 Second, fever and flu-like disease may result in an increased stroke risk because it can lead to systemic inflammation with endothelial dysfunction, a prothrombotic condition and increased platelet activation and aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It was found that various factors could suddenly increase blood pressure and trigger acute vessel rupture, resulting in intracranial haemorrhage, which exhibited as emotional changes, vigorous activity, sexual activity and Valsalva manoeuvres. 4 A case-crossover study (CCOS) design treats every participant as their own control to avoid individual differences, and this approach is widely used to test trigger factors. 5 Since Robinson et al 6 first reported an increased bAVM-related haemorrhage rate in females during pregnancy, pregnancy and WHAT IS ALREADY KNOWN ON THIS TOPIC ⇒ It has been reported that pregnancy and puerperium are associated with brain arteriovenous malformation (bAVM)-related haemorrhage; however, the results of existing studies are controversial, some even contradictory.…”
Section: Introductionmentioning
confidence: 99%